Graft Copolymerization of Natural Rubber With Functionalized Glycidyl Methacrylate Via Thermal and Free Radical Initiation: Effect of Processing Temperatures and Times - Nasirsah Nasirsah; Fatma Suryani Harahap; Muhammad Darwis; Iskandar Safri Hasibuan; Syahruddin Aritonang (Elkawnie, 2025)
Abstract: As an unsaturated elastomer, the natural rubber (NR) is difficult to maintain adhesivity with the other additive materials, limiting their use during the process of manufacturing. Therefore, it is necessary to modify the surface to improve thermal and oxidative resistance. This study aims to modify the natural rubber through a functionalization of glycidyl methacrylate (GMA) and its effect on temperatures and times during processing. Functionalization of NR was carried out via free radical initiation by varying the working times and temperatures. Characterizations via FTIR were performed to confirm the functional groups of NR and functionalized NR, while the analysis of grafting was carried out to describe the propose proposed reaction mechanisms. FTIR spectra confirmed the presence of functional groups contributing to NR including stretching O-H of peptide group (3285 cm-1), stretching and absorption of CH3 (respectively 2725 cm-1 and 1456 cm-1), and functionalized GMA were observed after functionalization (1730 cm-1). Working times and temperatures allowed the GMA to disperse evenly, resulting higher chance of homo-polymerisation via crosslinking of poly-GMA, optimum at 160-190oC. In conclusion, the thermal initiation process at the optimum temperature allows the maximum grafting degree of GMA on NR, reaching up to 80% at 170°C, and results in a much more stable reaction through free radical initiation. Abstrak: Sebagai salah satu elastomer tak jenuh, karet alam (NR) terbatas dalam menjaga kemampuan daya rekatnya dengan bahan aditif lain, sehingga membatasi penggunaan praktisnya dalam proses manufaktur. Oleh karena itu, diperlukan modifikasi khususnya di permukaan untuk meningkatkan ketahanan terhadap panas dan oksidasi. Penelitian ini bertujuan untuk memodifikasi NR melalui fungsionalisasi clycidyl metacrylate (GMA) dan mengkaji pengaruh suhu dan waktu selama proses fungsionalisasi berlangsung. Fungsionalisasi NR diinisiasi melalui radikal bebas dengan variasi waktu dan suhu reaksi. Karakterisasi menggunakan FTIR dilakukan untuk mengkonfirmasi keberadaan gugus fungsi pada NR dan NR-terfungsionalisasi, sedangkan analisis grafting dilakukan untuk menjelaskan mekanisme reaksi yang diusulkan. Spektra FTIR menunjukkan adanya gugus fungsi pada NR berupa regangan O–H (3285 cm⁻¹), regangan dan serapan CH₃ (masing-masing pada 2725 cm⁻¹ dan 1456 cm⁻¹), serta munculnya puncak khas GMA-terfungsionalisasi pada 1730 cm⁻¹. Variasi waktu dan suhu reaksi memungkinkan terjadinya dispersi GMA yang lebih merata, meningkatkan peluang terjadinya homopolimerisasi melalui ikatan silang poli-GMA, pada suhu 160–190°C. Secara keseluruhan, proses inisiasi termal pada suhu optimum menghasilkan derajat grafting maksimum GMA pada NR hingga 80% pada 170°C, serta menghasilkan reaksi yang lebih stabil melalui mekanisme inisiasi radikal bebas.